An Object Oriented Process Planning System for Rotational Components - P. C. Pandey; Nahid Rumana (Communications - Scientific letters of the University of Zilina, 2000)
This study presents an object oriented approach for the development of a process planning system for axis symmetric rotational components. The system consists of two modules: Part design data and manufacturing data input module and Object oriented process planning module (OOPP). Part data input module is created in customised AutoCAD environment. All the information about the input in the AutoCAD can be exported as DXF output file. DXF output file is automatically postprocessed in OOPP module to create object classes according to the input from this module. These classes are used by the sub modules: e.g., extraction of machinable volumes, setup planning, sequencing of operations, machine selection, tool selection and machining time calculation.